Human Myeloma Cell Lines Induce Osteoblast Downregulation of CD99 Which Is Involved in Osteoblast Formation and Activity - Angela Oranger; Giacomina Brunetti; Claudia Carbone; Graziana Colaianni; Teresa Mongelli; Isabella Gigante; Roberto Tamma; Giorgio Mori; Adriana Di Benedetto; Marika Sciandra; Selena Ventura; Katia Scotlandi; et al. (Journal of Immunology Research)
CD99 is a transmembrane glycoprotein expressed in physiological conditions by cells of different tissues, including osteoblasts (OBs). High or low CD99 levels have been detected in various pathological conditions, and the supernatant of some carcinoma cell lines can modulate CD99 expression in OB-like cells. In the present work we demonstrate for the first time that two different human myeloma cell lines (H929 and U266) and, in a less degree, their conditioned media significantly downregulate CD99 expression in normal human OBs during the differentiation process. In the same experimental conditions the OBs display a less differentiated phenotype as demonstrated by the decreased expression of RUNX2 and Collagen I. On the contrary, when CD99 was activated by using a specific agonist antibody, the OBs become more active as demonstrated by the upregulation of Alkaline Phosphatase, Collagen I, RUNX2, and JUND expression. Furthermore, we demonstrate that the activation of CD99 is able to induce the phosphorylation of ERK 1/2 and AKT intracellular signal transduction molecules in the OBs.